Analisis Faktor-Faktor Yang Mempengaruhi Motif Belanja Secara Online di Kalangan Mahasiswa di Kota Solo - Fransiske, Mona Windi; Hendratmoko, Christiawan; Kusasih, Ida Ayu Kade R. (STIE Surakarta, 2015)
One of the development of internet usage is spending on goods and services by online. This study aims to determine the effect of consumerâs confidence, product quality, economic status and knowledge of internet technologies towards online shopping patterns among students in Surakarta. This study used a sample of 100 respondents. The results indicate that consumerâs confidence, quality products and knowledge of internet technologiesare positive and significant effect towards online shopping patterns, while the economic status has positive but not significant effect towards the motive of shopping online. The coefficient of determination shows online shopping motive 46.4% influenced by variables that have studied